Influence of carrion smell and rebaiting time on the efficiency of pitfall traps to dung beetle sampling - Hector Flechtmann, Carlos Alberto [UNESP]; Tabet, Vinicius Gomes [UNESP]; Quintero, Ingrid [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) are very useful insects, as they improve the chemo-physical properties of soil, clean pastures from dung pads, and help control symbovine flies associated with bovine cattle. Their importance makes it fundamental to sample and survey them adequately. The objectives of the present study were to determine the influence of decaying insects trapped in pitfalls on the attractiveness of Moura pig Sus scrofa L. (Suidae) and collared peccary Tayassu tajacu (L.) (Tayassuidae) dung used as baits to lure dung beetles, and to establish how long these baits remain attractive to dung beetles when used in these traps. Some dung beetle species seemed to be able to discriminate against foul smell from decaying insects within the first 24 h, hence decreasing trap efficiency. This was more evident in peccary dung-baited traps, which proved to be the least attractive bait. Attractiveness lasted only 24 h for peccary dung, after which it became unattractive, whereas the pig dung bait was highly attractive for 48 h, after which its attractiveness diminished but was not completely lost.
Keywords: coprophagous beetles; sampling protocol; dung attractiveness; trap effectiveness; Coleoptera; Scarabaeidae; Scarabaeinae; Sus scrofa; Tayassu tajacu